P027 Comparing 10 Hz tACS and cathodal tDCS over right parietal cortex in their ability to affect pseudoneglect. Issue 3 (March 2017) - Veniero, D.; Benwell, C.S.Y.; Ahrens, M.M.; Thut, G.
Abstract : Question: Transcranial electrical stimulation is under investigation as an experimental and clinical interventional technique in both healthy participants and patients. While the technique is promising in many regards, important limitations have been identified, including weak effects as well as high inter- and intra-individual variability, hence the effort of many studies to enhance its effectivity. Here, we directly compared two "inhibitory" tES techniques with supposedly different mechanisms of action as to their effectivity of intervention into a cognitive task. Methods: Nineteen healthy participants underwent transcranial alternating current stimulation at alpha frequency (10 Hz-tACS) shown to entrain the "inhibitory" alpha oscillation or cathodal transcranial direct current stimulation (c-tDCS) known to supress neuronal spiking activity, as well as a tES control (sham). tES was applied for 10 min with a right parietal stimulation - left frontal return montage (electrode sizes: 3 × 3 cm–7 × 5 cm), while participants were performing a perceptual line bisection (landmark) task. The tES protocols were compared as to their ability to interfere with left pseudoneglect in healthy participant, the latter thought to be under control of the right hemisphere. Results: The results revealed that only right parietal 10 Hz-tACS led to the expected changes in spatial attention bias, namely a rightward shift in line bisection (as compares to sham). No effects of right parietal c-tDCS were observed. While the rightward attention shifts by 10 Hz-tACS were observed in the majority of participants ( n = 14), the mean amplitude of this shift was small (as compared to the range of spatial attention biases in the healthy population), speaking for weak, albeit significant changes. Conclusions: Our study suggests that more direct comparisons across protocols are needed in an attempt to improve tES techniques.